PENGEMBANGAN MEDIA PEMBELAJARAN LUDO PADA MATA PELAJARAN EKONOMI KELAS XI SMA PURNAMA TRIMURJO - Sri Armiyanti Ningsih; Meyta Pritandhari (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of this study is to produce avalid medium used asean economic learning medium. This research isa development (research and development) with 4D development model (sugiyono 2015:37) the development stage consists of define, design, development and disesminstion. Ludo learning media is assessed feasbility by 2 experts consisting of two lectures, a material expert consisting of one subject economics teacher, and 15 students ofclass XI SMA Purnama Trimurjo were tested in small groups.the results of the overal datawere 84% validation of ludo media exprets, 74% initialmaterial expert validation, 79% final material validation, 91% of learners responses during small group trials. I can be concluded ludo learning media worthy of use asa a medium of economic learning and can facilitate learners in learning activites. Keywords: Development, Learning of Media, Ludo